Protective Immunity in Mice Immunized With P. vivax MSP119-Based Formulations and Challenged With P. berghei Expressing PvMSP119 - Dobrescu, Irina; de Camargo, Tarsila Mendes; Gimenez, Alba Marina; Murillo, Oscar; Amorim, Kelly Nazaré da Silva; Marinho, Claudio Romero Farias; Soares, Irene Silva; Boscardin, Silvia Beatriz; Bargieri, Daniel Youssef (Frontiers in Immunology, 2020)
The lack of continuous in vitro cultures has been an obstacle delaying pre-clinical testing of P. vivax vaccine formulations based on known antigens. In this study, we generated a model to test available formulations based on the P. vivax MSP1(19) antigen. The P. berghei strains ANKA and NK65 were modified to express PvMSP1(19) instead of the endogenous PbMSP1(19). The hybrid parasites were used to challenge C57BL/6 or BALB/c mice immunized with PvMSP1(19)-based vaccine formulations. The PvMSP1(19) was correctly expressed in the P. berghei hybrid mutant lines as confirmed by immunofluorescence using anti-PvMSP1(19) monoclonal antibodies and by western blot. Replacement of the PbMSP1(19) by the PvMSP1(19) had no impact on asexual growth in vivo. High titers of specific antibodies to PvMSP1(19) were not sufficient to control initial parasitemia in the immunized mice, but late parasitemia control and a balanced inflammatory process protected these mice from dying, suggesting that an established immune response to PvMSP1(19) in this model can help immunity mounted later during infection.